Synthesis and antibacterial evaluation of sulfonamide bridged disubstituted 1, 2, 3-triazoles. Issue 24 (17th December 2022) - Yadav, Archna; Kaushik, C. P.
Abstract: In the present study, a series of sulfonamide bridged 1, 4-disubstituted 1, 2, 3-triazoles have been synthesized in good yield via click reaction between sulfonamide linked terminal alkynes and in situ prepared 2/3/4-azidobenzenesulfonamides. The synthesized triazoles were characterized by FTIR, 1 H NMR, 13 C NMR, and HRMS techniques. Further, all the synthesized compounds were assessed for in vitro antibacterial activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Klebsiella pneumonia . It has been observed that some of the synthesized triazoles possess appreciable efficacy against the bacterial strains used. Particularly, compound 4-bromo- N -((1-(4-(sulfamoylphenyl)-1 H -1, 2, 3-triazol-4-yl)methyl)benzenesulfonamide 6l (MIC = 0.132 µmol/mL) revealed significant antibacterial activity against B. subtilis, E. coli, and K. pneumonia. Further, the molecular docking study of the above potent compound was also performed in the active site of the enzyme dihydropteroate synthase to have the possible mode of action. Graphical Abstract: UF0001